Pengaruh Parameter Proses Pengecoran Squeeze (Temperatur Tuang, Temperatur Cetakan dan Kandungan Si) Terhadap Struktur Mikro, Kekerasan dan Kekuatan Tarik pada Benda Cor Tipis Al-Si - Elfendri - (Jurnal APTEK, 2011)
The objective of this is to study the effects of melt temperature, die temperature and Si content) on microstructure, hardness and tensile strength in squeeze casting (direct squeeze casting) of thin casting material, Al-0.45%Si, Al-3.22%Si and Al-6.04%Si.The alloys were melted on crucible furnace and cast at the temperatures of 665°C, 775°C and 885°C, in die-punch mold heated at the temperatures of 220°C, 275°C and 330°C. Pressure of 135 MPa was applied to press liquid metal in the mold. Microstructure were observed by using optical microscope. Vickers’ hardness and tensile strength were conducted to identify mechanical properties.Results of the tests indicated increase in casting temperature causing increasingly thinner and globular silicone fragments, reduced hardness and tensile strength. The thicker silicone fragments, reduced hardness and tensile strength occurred with the intensifying temperature of the mold. Increase in Si content resulted in thicker and more abundant silicon flakes, intensifying hardness and tensile strength.